STUDY OF ACUTE TOXICITY, LOCAL IRRITANT AND ALLERGIZING EFFECTS OF THE SUBSTANCE "GLAUCONITE-NEO" - Umaraliyeva Nilufar Ravshan kizi,; Maksudova Firuza Khurshidovna,; Fayzullayeva Nodira Sultanovna,; Gulyamov Shokhid Sharafutdin ugli, (The Bioscan, 2025)
Based on the research results, the substance "Glauconite-Neo" (TashPharma, Uzbekistan) does not exhibit toxicity in the dose range of 2000–4000 mg/kg according to acute toxicity indicators. Even at maximum doses, it does not lead to animal death, does not have a local irritant effect when applied, and does not have an allergenic effect.